The Right of the Lessor to Reclaim the Leased Property under a Financial Leasing Contract in Accordance with Palestinian Law: A Comparative Study with Jordanian and Egyptian Law - Qabaha, Amjad Subhi Taher (Dirasat: Shari'a and Law Sciences, 2025)
Objectives: This study examines the legal framework governing the lessor’s right to reclaim leased property under financial leasing contracts in Palestinian law, comparing it with the provisions in Jordanian and Egyptian legislation. It analyzes the mechanisms for property reclamation upon contract expiration and the legal procedures required for termination due to breaches. The study also explores the lessor’s obligation to notify the lessee of any violations leading to contract termination and the formal requirements for reclaiming the leased property. Methods: The research employs an analytical and comparative approach, examining the relevant legal provisions in Palestinian, Jordanian, and Egyptian law to identify similarities and differences in the regulation of financial leasing contracts. Results: The findings indicate that Palestinian law provides specific legal provisions for financial leasing contracts, distinguishing them from other types of agreements regarding property reclamation. The law grants contractual freedom to both parties, allowing flexibility in defining terms. Additionally, it outlines distinct litigation procedures for reclaiming leased property, ensuring alignment with the unique nature of financial leasing contracts. Conclusions: Palestinian law establishes a structured legal framework for financial leasing, balancing the rights of both lessors and lessees. It incorporates specific provisions for reclaiming leased property while allowing contractual flexibility. The study highlights key differences and similarities between Palestinian, Jordanian, and Egyptian legal frameworks, offering insights for legislative improvements and harmonization.